PEREMPUAN DI BALIK KABUT BROMO: Membaca Peran Aktif Perempuan Tengger dalam Kehidupan Rumah Tangga dan Masyarakat - Ikwan Setiawan (Humaniora, 2008)
This article is an ethnographic study of Tengger women in Wonokerso, Sumber, Probolinggo, East Java. It focuses on some significant and active roles of Tengger women, especially in the household, society, and traditional rites. The data for the research were obtained through interviews with some informants and participatory observation. The results show that Tengger women have some significant roles in taking care their families, especially in managing their family welfare and children’s education, participating in social life, and conducting traditional rites as the key to find an equilibrium of life; a conducive and strategic collaboration between traditional commitments and economic motivation in order to have a better familial and socio-cultural life.